The equation could represent p is P(x) = (x+3)(x-2)^2
The brackets indicate where the curve will intersect the x-axis.
The curve intersects the graph at (0,-3) and (0,2).
That is to say:
x = -3
AND
x = 2
Rearrange the equations so that they equal 0.
x + 3 = 0
x - 2 = 0
The values in the brackets will be used.
We know that x - 2 is a repeating root because the curve only touches it and does not cross it, hence (x-2) is squared.
As a result, your brackets are as follows: (x+3)(x-2)(x-2)
Which of the following can be simplified:
(x+3)(x-2)^2
Where 2 denotes squared.